CT-based nomogram predicts esophageal gastric variceal bleeding in noncirrhotic portal hypertension caused by hepatic schistosomiasis - Wei Cheng; Ke-Ying Wang; Wen-Qiang Li; Yao Li; Xiao-Yan Li; Shuai Ju (BMC Medical Informatics and Decision Making)
Abstract Background To construct a nomogram combining CT varices vein evaluation and clinical laboratory tests for predicting the risk of esophageal gastric variceal bleeding (EGVB) in patients with noncirrhotic portal hypertension (NCPH). Methods A total of 315 NCPH patients with non-EGVB and EGVB were retrospectively enrolled and randomly divided into training and testing cohorts. Thirteen collateral vessels were identified and evaluated after CT portal vein system reconstruction. Multivariate binary logistic regression analysis was used to choose CT images and clinical predictors of EGVB. The varices score of each patient was calculated. A nomogram was built by combining the varices score with the selected clinical predictors of EGVB. The receiver operating characteristic (ROC) curve was used to evaluate the predictive performance of the nomogram. Results Platelet count and prothrombin time were selected as clinical predictors; the esophageal vein, gastroepiploic vein and omental vein were selected as CT image predictors for predicting EGVB. A reduced platelet count, prolonged prothrombin time, severe esophageal and gastroepiploic vein tortuosity and less omental vein tortuosity were predictors of EGVB in NCPH patients. The specificity, sensitivity, negative predictive value, positive predictive value and AUC of the ROC of the nomogram were 0.82, 0.81, 0.89, 0.70, and 0.88 (95% CI: 0.84–0.93) in the training cohort and 0.87, 0.86, 0.88, 0.84, and 0.91 (95% CI: 0.84–0.97) in the testing cohort, respectively. Conclusions The nomogram combining CT images and clinical predictors could be useful to individualize and predict the risk of EGVB in NCPH patients. Clinical relevance statement Results showed that the nomogram combining CT-evaluated collateral vessels (varices score) and clinical laboratory tests could be used to realize personalized prediction of first-time EGVB in NCPH patients.